Slang Variations in Dax’s Song Lyrics: A Sociolinguistic Analysis - Abdul Manan Musa; Muziatun; Jefriyanto Saud (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the sociolinguistic functions of slang variations in the lyrical repertoire of rapper Dax, an artist notably absent from existing academic literature despite his significant cultural impact. Applying Eble’s theoretical framework of slang effects, this research employs qualitative analysis of four commercially successful songs spanning Dax’s creative evolution from 2018 to 2023. The methodology integrates computational screening with rigorous validation through Green’s Dictionary of Slang, ensuring lexicographical authority. Findings reveal 27 validated slang expressions functioning as sophisticated rhetorical instruments that simultaneously cultivate informality, signal group identification, and articulate opposition to authority. The analysis demonstrates Dax’s artistic progression from establishing hip-hop authenticity through multifaceted slang usage toward more focused explorations of spiritual turmoil and systemic critique. Theoretically, this study extends Eble’s framework to contemporary musical discourse, revealing slang’s multidimensional role in constructing identity and negotiating social meaning. Practically, it offers pedagogical applications for bridging sociolinguistic theory with authentic language practices. This investigation advances the field by documenting understudied linguistic phenomena in popular culture while providing a replicable model for analyzing vernacular speech in artistic contexts.